Organizaciones que aprenden: Nivel educativo medio superior del sector privado (Learning organizations: Private high school level) - Mata, Rogelio; Lafuente, Roy; Ruiz, Fernando (UANL. Facultad de Contaduría Pública y Administración, 2016)
Abstract. To convert an educational institution, such as the private high school, an organization that learns, we must know the school, their strengths, opportunities, to support change, threats, weaknesses that impede it, starting from the individual learning to organizational, because both have an impact on a learner organization, involving all elements such as leadership, work in equipment, resources, culture and values that they make and provide structure, as well as the context in which this immersed; the process of internal learning which characterized them and provide scaffolding, of the new acquisition that they help you or in the future helping you to become the type of organization that not only will be able to adapt to the demands of a modern and dynamic society, but also to transform to generate meaningful learning, allowing it to be competent permanent and relevant to developing its capacities and the survival skills. Resumen. Para convertir una institución educativa, como el bachillerato privado, en una organización que aprende, debemos de conocer la escuela, sus fortalezas, las oportunidades, que apoyarán el cambio, las amenazas, las debilidades que lo impedirán, partiendo desde el aprendizaje individual hasta el organizativo, porque ambos inciden en una organización aprendiente, involucrando todos los elementos como el liderazgo, trabajo en equipo, recursos, cultura y valores, que la conforman y le proporcionan estructura, así como el contexto en el cual está inmerso; los proceso de aprendizaje internos que los caracterizan y le brindan andamiaje, a los de nueva adquisición que le ayudan o en un futuro le auxiliaran a convertirse, en el tipo de organización que no solo será capaz de adaptarse a las exigencias de una sociedad moderna y dinámica, sino también a transformarse para generar el aprendizaje significativo, permitiéndole ser competente, permanente y pertinente desarrollando sus capacidades y habilidades para la supervivencia.